Carrier phase GNSS attitude determination with the multivariate constrained LAMBDA method - Giorgi, G.; Teunissen, Peter (2010)
Carrier phase integer ambiguity resolution is the key to fast and high-precision GNSS positioning and navigation. It is the process of resolving the unknown cycle ambiguities of the double-differenced carrier phase data as integers. The popular LAMBDA method is an efficient algorithm that is used to resolve the integer ambiguities, and is known to maximize the ambiguity success rate. The method has been modified to be applicable to attitude determination problems, where all the nonlinear constraints have been fully integrated into the objective function and corresponding integer search. The method is tested processing data collected on static as well as dynamic platforms, focusing on the stand-alone, unaided, single-frequency, single-epoch case, as this is the most challenging scenario for attitude ambiguity resolution. ©2010 IEEE.